The Application Of Criminal Sanctions In Environmental Pollution Cases: A Justice-Based Analysis Of Decision No. 321/PID.SUS/LH/2025/PN BDG - Apud Abdul Aziz; Suyud Margono; Hotman Sinambela (Institute of Advanced Knowledge and Science, 2026)
This study examines the application of criminal sanctions in an environmental pollution case from the perspective of justice, focusing on Decision No. 321/Pid.Sus/LH/2025/PN Bdg involving PT Mitra Light Block. The issue is significant because environmental criminal law is expected not only to enforce statutory compliance but also to ensure that punishment is imposed in a fair, proportionate, and legally reasoned manner. This article aims to analyze the correlation between environmental law enforcement and the principle of justice in the imposition of criminal sanctions. The study employs normative legal research using statute, conceptual, and case approaches. The analysis is based on primary legal materials, including statutory regulations and the court decision, as well as secondary legal materials in the form of legal doctrines and scholarly literature. The findings indicate that the application of criminal sanctions in environmental cases cannot be assessed solely on the basis of formal statutory violation. It must also consider culpability, proportionality, environmental risk, judicial reasoning, and the broader public interest protected by environmental law. The case demonstrates that although the prohibited act was legally established, the question of justice remains closely tied to the relationship between the unlawful conduct, the degree of harm, and the reasoning underlying the sanction. This study concludes that a justice-based approach to environmental criminal law requires punishment to reflect not only legal certainty but also substantive fairness in responding to environmental violations.